Sequentially Bornological Compact Space - Kamil Al-Basri, Fatma (Al-Qadisiyah Journal of Pure Science, 2018)
In this paper, we introduce the definitions of sequentially bornological continuous mapping and sequentially bornological compact spaces in bornological vector space. We investigate the properties of these concepts. Also, we give the relation between sequentially bornological compact spaces and complete bornological vector spaces.